Rapid Endothelialization of Off-the-Shelf Small Diameter Silk Vascular Grafts - Elysse C. Filipe, MSc; Miguel Santos, MSc; Juichien Hung, MSc; Bob S.L. Lee, MSc; Nianji Yang, MPhil; Alex H.P. Chan, BSc; Martin K.C. Ng, MD, PhD; Jelena Rnjak-Kovacina, PhD; Steven G. Wise, PhD (JACC: Basic to Translational Science, 2018)
Synthetic vascular grafts for small diameter revascularization are lacking. Clinically available conduits expanded polytetrafluorethylene and Dacron fail acutely due to thrombosis and in the longer term from neointimal hyperplasia. We report the bioengineering of a cell-free, silk-based vascular graft. In vitro we demonstrate strong, elastic silk conduits that support rapid endothelial cell attachment and spreading while simultaneously resisting blood clot and fibrin network formation. In vivo rat studies show complete graft patency at all time points, rapid endothelialization, and stabilization and contraction of neointimal hyperplasia. These studies show the potential of silk as an off-the-shelf small diameter vascular graft.